11 YEARS OF BIOSTEREOLOGY IN CHINA - Shen, Hong (Image Analysis and Stereology, 2011)
Biostereology in China is very active. Here is a brief summary: Organization: The organization of biostereology in China was founded in Nov. 1988. Its name is Chinese Society of Biomedical Stereology (CSBS), and is affiliated to the Chinese Society for Stereology (CSS). The first joint president of CSS/BMC was Prof. Peixuan Tang, the second and now the third, is Prof. Dewen Wang. There are 556 registered members. Academic Congresses: Sessions of the National Biostereological Congress were convened in 1990, 1992, 1996 and 2000. Publications: Four works were written and published in China. One is "Quantitative Histology" (Luji Shi, 1964), another is "Stereological Morphometry For Cell Morphology" (Fusheng Zheng, 1990), the third one is "Practical Biostereological Techniques" (Hong Shen and Yingzhong Shen, 1991) and the fourth one is "Quantitative Cytology and Cytochemistry Techniques" (Genxing Xu, 1994). A Chinese Journal of Stereology and Image Analysis has been published since 1996. Courses: More than ten national training courses on biostereology were held. In some medical universities or colleges, a biostereology course has been set up. Theoretical studies: Some new concepts, parameters and methods for stereology and morphometry were put forward, such as: regular form factor, volume concavity, surface concavity, area concavity, boundary concavity, curve profile area density, positive university for immunohistochemistry stain etc. Application: Stereological methods have been widely applied in biomedical studies. The applied field covered most of the morphological domain of biology. The main applications of biostereology are quantitative pathological diagnosis and prognosis of tumor cells and histostructures. Most studies utilize classical stereological methods. New stereological methods should be popularized and applied in the future. Image Analysis System: Image analysis systems are widely used in biostereological studies. About ten kinds of image analysis systems have been manufactured in China. The most popular is HPIAS, which is made by Huahai Electronic CO.LTD.